Development of E-Modules on Problem-Based Learning to Enhance Students Science Literacy - Asnidar, Asnidar; Safriana, Safriana; Jalil, Saifuddin Muhammad; Sakdiah, Halimatus; Zahara, Syarifah Rita (Asian Journal of Science Education, 2024)
Interactive electronic modules are teaching materials used in the learning process with the help of today's technology which is useful for forming a more creative learning process. This development research method refers to Research and Development (RD) with the ADDIE model. The research subjects were 11th-grade Science 4, totalling 31 students and the research objects were located at Kejuruan Muda Public High School 1. Data collection instruments in the form of pretest and post-test and an interest questionnaire regarding the e-module. Data analysis is qualitative data analysis and quantitative data analysis. The results obtained are from material experts in the "Decent" category, while validation results from media experts are in the "Decent" category. the results of the teacher's response in the "Very Interesting" category and the results of the student's response in the "Very Interesting" category. The N-gain test carried out in 11th-grade Science 4 obtained a result of 0.70 with a percentage of 70% falling into the "High" category. The results of this research indicate that the development of an interactive electronic module based on problem-based learning on material elasticity of materials and Hooke's law is suitable for use and can increase students' scientific literacy.